The Research of Microgrid Optimized Dispatching Method Based on MEA - Zhang, Shao Min; Wang, Bao Yi; Wei, Chen (Applied Mechanics and Materials, 2014)
Integration of large scale renewable energy sources and electric cars into power grid will bring new opportunities and challenges to the operation, control of the power grid and the power market .The microgrid , which integration the distributed generation systems, energy storage element and loads ,has been seen as one effective way to solve the problems. This paper proposed a MEA-based scheduling algorithm, and studied a microgrid that contains 32 nodes and 50 electric cars. Both the MEA algorithm and mixed integer nonlinear programming algorithm (MINLP) can solve the energy resource scheduling problem,but the results of our simulation shows that the total cost of MEA is higher than that of the MINLP,but there is a significant improvement in the efficiency of execution.The results shows that we can use MEA to achieve optimal scheduling,it also verify the effectiveness of the algorithm.